Effects of encapsulation on the viability of probiotic strains exposed to lethal conditions - Borges, Sandra (2019)
The eﬀect of microencapsulation on the viability of Lactobacillus casei, L. paracasei, L. acidophilus Ki and Biﬁdobacterium animalis BB-12 during exposure to lethal conditions (25% NaCl, pH 3.0 and 55–60 C) was evaluated. Results demonstrated that survival of probiotic strains to the imposed lethal stress conditions was strain dependent. With the exception of exposure to 25% (w⁄v) NaCl, L. acidophilus Ki (free and encapsulated cells) demonstrated the highest survival rates through exposure to lethal conditions of temperature and pH. For this probiotic strain exposed to heat, microencapsulated cells expressed a higher heat tolerance at 55 C than free cells. For the other tested bacteria, in general, encapsulation had no positive eﬀect on survival through the tested lethal conditions.